Pelatihan bisnis digital marketing di PT. Abisakti Surya Megakon - Yudianto, Firman; Magfira, Dike Bayu; Adinugroho, Mukhtar; Herlambang, Teguh; Yuliana, Leni (Indonesia Berdaya, 2023)
Digital marketing is a marketing strategy using the internet and information technology to expand traditional marketing functions. Digital marketing can help marketers establish relationships with customers to increase customer loyalty. Digital Marketing is one of the media that is currently in great demand by the public and as a support in their daily activities. Gradually, many people are starting to leave conventional marketing methods and switch to digital marketing. The problems experienced by PT. ASM is about digital marketing business marketing that can increase revenue on a sustainable scale in the era of globalization. This training will be given to employees / HR from PT. ASM to be able to improve soft skills in implementing and developing digital marketing so that it can help receive all forms of scientific and technological information that comes from outside to improve the economy for future prosperity. This training will be provided in a hybrid manner, conducted offline or online (zoom). This training will explain in more depth about digital marketing. Participants will also be taught to develop strategies to communicate brands through various digital media, as well as evaluate and measure their level of success.